2017
DOI: 10.2306/scienceasia1513-1874.2017.43.207
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of domoic acid in marine organisms from Sriracha bay, Chonburi province, Thailand

Abstract: Domoic acid (DA), a toxin produced by diatoms Pseudo-nitzschia and Nitzschia, causes amnesic shellfish poisoning. DA accumulated in marine organisms from Sriracha bay, Chonburi province, Thailand was determined from May 2012 to July 2013. Field surveys and sample collections were conducted every two months. DA content was determined using the enzyme linked immunosorbent assay (ELISA) method and ranged between not detectable and 110 ng/l for plankton. DA content in zooplankton ranged between 0.04 and 0.21 ng/l … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
0
0
0
Order By: Relevance
“…DA contamination has also been reported in both wild and cultivated shellfish in many European countries, such as: M. edulis galloprovincialis and Donax trunculus in 1999, in France [11]; Cerastoderma edule and Venerupis pullastra in 2000, in Portugal [12]; M. galloprovincialis in 2000-2004, in Italy [13]; M. edulis and Pecten maximus in 2001-2022, in Scotland [14]; M. galloprovincialis and Venus verucosa in 2002, in Greece [15]; P. maximus in 2003-2004 [16], Callista chione and D. trunculus in 2008-2011 [17], in Spain; and M. galloprovincialis in 2011, in Croatia [18]. In Asia, the prevalence of DA contamination has also been reported in: M. galloprovincialis in 2018-2019, in Turkey [19]; Perna viridis, Crassostrea lugubris, and Pinctada fucata in 2012-2013, in Thailand [20]; and M. trossulus and Mizuhopecten yessoensis in 2009-2010, in Russia [21]. A survey in Angola showed DA contamination in Dosinia orbignyi Dunker, V. corrugate Gmelin and Mactra glabrata L. in 2007 [22].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…DA contamination has also been reported in both wild and cultivated shellfish in many European countries, such as: M. edulis galloprovincialis and Donax trunculus in 1999, in France [11]; Cerastoderma edule and Venerupis pullastra in 2000, in Portugal [12]; M. galloprovincialis in 2000-2004, in Italy [13]; M. edulis and Pecten maximus in 2001-2022, in Scotland [14]; M. galloprovincialis and Venus verucosa in 2002, in Greece [15]; P. maximus in 2003-2004 [16], Callista chione and D. trunculus in 2008-2011 [17], in Spain; and M. galloprovincialis in 2011, in Croatia [18]. In Asia, the prevalence of DA contamination has also been reported in: M. galloprovincialis in 2018-2019, in Turkey [19]; Perna viridis, Crassostrea lugubris, and Pinctada fucata in 2012-2013, in Thailand [20]; and M. trossulus and Mizuhopecten yessoensis in 2009-2010, in Russia [21]. A survey in Angola showed DA contamination in Dosinia orbignyi Dunker, V. corrugate Gmelin and Mactra glabrata L. in 2007 [22].…”
Section: Introductionmentioning
confidence: 97%
“…Studies have shown that different shellfish accumulate different levels of DA in their tissues [20,24], probably due to different accumulation and elimination rates and differences in the distribution of DA in the various tissues [25]. In many bivalves, most of the DA accumulates in the digestive gland, which is the main site of metabolic elimination [26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%